When “He” can also be “She”: an ERP study of reflexive pronoun resolution in written mandarin Chinese - Su, Jui-Ju; Molinaro, Nicola; Gillon-Dowens, Margaret; Tsai, Pei-Shu; Wu, Denise H.; Carreiras, Manuel (Frontiers Media, 2016)
The gender information in written Chinese third person pronouns is not symmetrically encoded: the character for "he" (, with semantic radical , meaning human) is used as a default referring to every individual, while the character for "she" (, with semantic radical , meaning woman) indicates females only. This critical feature could result in different patterns of processing of gender information in text, but this is an issue that has seldom been addressed in psycholinguistics. In Chinese, the written forms of the reflexive pronouns are composed of a pronoun plus the reflexive "/self" (/himself and /herself). The present study focuses on how such gender specificity interacts with the gender type of an antecedent, whether definitional (proper name) or stereotypical (stereotypical role noun) during reflexive pronoun resolution. In this event-related potential (ERP) study, gender congruity between a reflexive pronoun and its antecedent was studied by manipulating the gender type of antecedents and the gender specificity of reflexive pronouns (default: /himself vs. specific: /herself). Results included a P200 "attention related" congruity effect for /himself and a P600 "integration difficulty" congruity effect for /herself. Reflexive pronoun specificity independently affected the P200 and N400 components. These results highlight the role of /himself as a default applicable to both genders and indicate that only the processing of /herself supports a two-stage model for anaphor resolution. While both reflexive pronouns are evaluated at the bonding stage, the processing of the gender-specific reflexive pronoun is completed in the resolution stage.